2021
DOI: 10.31234/osf.io/rs43g
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Measuring Growth Mindset: A Validation of a Three-item Scale and a Single-item Scale in Youth and Adults

Abstract: A growth mindset is the belief that personal characteristics, specifically intellectual ability, are malleable and can be developed by investing time and effort. In recent decades, numerous studies have investigated the associations between growth mindset and academic achievement, and large intervention programs have been established to train adolescents to develop a stronger growth mindset. However, methodological research on the adequacy of the measures used to assess growth mindset is scarce. In our study, … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 23 publications
4
9
0
Order By: Relevance
“…Furthermore, PISA 2018 measured fixed mindset with a single item in the PISA2018 survey -the first time that PISA included an implicit theory measure. Rammstedt et al (2021) provided preliminary evidence that both the most widely used three-item (Dweck et al, 1995) and single-item fixed mindset measures (i.e., the same one as the PISA used) had acceptable psychometric properties in terms of reliability, comparability, and validity for German adolescents. Nevertheless, the psychometric validity of the single-item fixed mindset scale for other countries is still unknown.…”
Section: Map Goals and Their Antecedentsmentioning
confidence: 93%
“…Furthermore, PISA 2018 measured fixed mindset with a single item in the PISA2018 survey -the first time that PISA included an implicit theory measure. Rammstedt et al (2021) provided preliminary evidence that both the most widely used three-item (Dweck et al, 1995) and single-item fixed mindset measures (i.e., the same one as the PISA used) had acceptable psychometric properties in terms of reliability, comparability, and validity for German adolescents. Nevertheless, the psychometric validity of the single-item fixed mindset scale for other countries is still unknown.…”
Section: Map Goals and Their Antecedentsmentioning
confidence: 93%
“…We reversed the score such that a higher score indicates stronger growth (vs. fixed) mindsets. Studies have demonstrated the reliability and validity of a single‐item measure of mindsets (Rammstedt et al, 2021).…”
Section: Methodsmentioning
confidence: 99%
“…Second, the conceptualization of measurement of growth (vs. fixed) mindset is limited in the current data set due to a single-item use of the mindsets, which may not fully represent the spectrum and dimensions of mindset beliefs (cf. Rammstedt et al, 2021). It is also possible that more complex belief systems that contribute to mindsets are embedded in different cultures (Bernardo et al, 2021;King et al, 2012;Lou et al, 2017).…”
Section: Limitationsmentioning
confidence: 99%
“…We caution against the use of single-item measures, given their limited reliability and the possible response bias (Rammstedt et al, 2021). If researchers wish to capture implicit theories more broadly, they should assess both mindsets and draw inferences on these two constructs rather than a unified construct.…”
Section: Implications For Using the Implicit Theories Of Intelligence Scalementioning
confidence: 99%
“…Clearly, such single-item measures are likely be prone to acquiescence bias and measurement error (OECD, 2021). In their study of three-and single-item measures of fixed mindsets, Rammstedt et al (2021) showed that the relations to other constructs can differ substantially between the two types of measures and that single-item measures suffer from low test-retest reliabilities. This practice also assumes the orthogonality of the two mindsets.…”
Section: Measurement Issuesmentioning
confidence: 99%